Galat Pendugaan Lalu Lintas Harian Rata-rata Berdasarkan Jumlah Hari Survei Merujuk pada Regulasi di Indonesia - Hendrawan, Hendra (MEDIA KOMUNIKASI TEKNIK SIPIL, 2025)
Road infrastructure is an important element that must be well planned where in its implementation it is faced with limited resources. Therefore, traffic surveys conducted for a full year to obtain the Average Annual Daily Traffic (AADT) value used in road planning and design are difficult to obtain. To overcome these obstacles, the government has set the number of survey days for two days and seven days depending on its designation. This study aims to determine the error in estimating the Average Daily Traffic (ADT) based on the number of survey days. Data were obtained through field surveys using an automatic vehicle counter with a tool error value of 10%. The errors calculated include MAE, MAPE, RMSE, and Bias. The results of the study show that the number of survey days affects the magnitude of the error and the range of ADT Bias in predicting the AADT value. The number of survey days for two days, three days, and seven days showed good predictions. The Bias Range as a correction factor for the estimated AADT value is influenced by traffic conditions during the year. The correction factor with 95% CI based on the recommended research results for Road Type 4/2T or 2/1 is in the interval (1.40;-1.59) for a 2-day survey, and (3.92;1.17) for a 7-day survey.